2006
DOI: 10.1177/1476718x06059788
|View full text |Cite
|
Sign up to set email alerts
|

parents’ experiences of a family literacy programme

Abstract: Relatively few studies of family literacy programmes have investigated parents’ views, despite their importance for the future development of this kind of programme in early childhood education. This article reports on a family literacy programme from the perspectives of the parents involved in it. The study was carried out in socio-economically disadvantaged communities in a northern English city. Parent experiences were investigated through interviews at the beginning and end of the programme ( N = 85) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 20 publications
4
35
0
2
Order By: Relevance
“…Implicit in the term 'family literacy' is the notion that a range of family members and generations will be engaged in some kind of literacy or numeracy learning (NIACE, 2003). However, this study and previous research consistently points to the fact that, Goldman, 2005;Hannon et al, 2006). Where programmes were designed for both adults and children the mother usually attended alone with just one child.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Implicit in the term 'family literacy' is the notion that a range of family members and generations will be engaged in some kind of literacy or numeracy learning (NIACE, 2003). However, this study and previous research consistently points to the fact that, Goldman, 2005;Hannon et al, 2006). Where programmes were designed for both adults and children the mother usually attended alone with just one child.…”
Section: Resultsmentioning
confidence: 58%
“…in Lincolnshire (Atkin et al, 2005). In England a substantial body of research has been undertaken into various programmes across the country, particularly research led by Brooks and Hannon, which has explored many aspects of family literacy (Brooks et al, 1997(Brooks et al, , 2002(Brooks et al, , 2004Hannon, 1999;Hannon & Bird, 2004;Hannon et al, 2006). However, few comparative crossEuropean studies have been conducted.…”
Section: A Theoretical Context For Family Literacymentioning
confidence: 97%
“…The "Framework For Early Literacy Development with Parents (FELDP)" project The FELDP [1], built on project in previous early literacy development work with families (Nutbrown et al, 2005;Morgan et al, 2009;Hannon et al, 2006) using a collaborative model of co-production. The ORIM Framework (Table I) was the organising concept of the FELDP project, which involved a nationally recruited group of 20 early years practitioners working in a range of contexts.…”
Section: )mentioning
confidence: 99%
“…This was obvious in the interviews' results because teachers indicated that the program was helpful in supporting school-family relations as it solved the problems related to the lack of parents' interest in reading books to children, and parents' inappropriate literacy expectations. This result is supported by the work of Hannon et al (2006) who indicated that parents of children expressed positive views about the effect of family literacy programs as they found these programs beneficial for young children. In the same context, Huss-Keeler (1997) established that parents have positive perceptions of being involved in the school.…”
Section: Discussionmentioning
confidence: 77%